RELEVANCE OF GANDHIAN ECO-VISION - Pushparajan , A (Journal of Dharma, 2006)
The relevance of M. K. Gandhi has been discussed ad-nauseam by various people in a variety of ways. For a few people today it has become a fashion to question the relevance of Gandhian thought. There is, however, an area which Gandhian relevance can never be disputed about. It is his ecological concerns. Even those who think that Gandhi is totally irrelevant and useless will have to accept his eco-vision.